In vitro metabolism of pyrrolizidine alkaloids – Metabolic degradation and GSH conjugate formation of different structure types. (January 2020) - Geburek, Ina; Preiss-Weigert, Angelika; Lahrssen-Wiederholt, Monika; Schrenk, Dieter; These, Anja
Abstract: Pyrrolizidine alkaloid (PA) forming plants are found worldwide and may contaminate food products at levels being of concern for human health. Due to the high biodiversity of PA producing plants many different types of PA structures are formed. PAs themselves are not toxic but require metabolic activation to exert toxicity. To investigate if the structure of the PAs affects their in vitro metabolism, we incubated a set of 22 PAs and compared the degradation rates and the amount of formed glutathione (GSH) conjugates. With human liver microsomes, no metabolic degradation of monoesters was found. Degradation rates of diester PAs tended to correlate with their hydrophilicity, whereby the more polar and branched-chained PAs exhibited lower degradation. There was a trend towards higher degradation rates in the presence of rat liver microsomes, but the GSH conjugate levels were similar. Although an effective degradation seems to be related with high GSH conjugate levels, no clear correlation between both parameters could be deduced. For both species no GSH conjugates, or only trace amounts, were formed from monoesters. However, for both open-chained as well as cyclic diesters GSH conjugates were detected and determined levels were comparable for both ester types without major structure-dependent differences. Highlights: The in vitro metabolism of 22 PA with human and rat liver microsomes was investigated. Species specific differences in degradation rates were obtained for monoesters. Both species showed similar levels of formed DHP-glutathione conjugates. DHP-glutathione conjugates have been detected mainly for PA-diesters but not for monoesters.